Intertextuality in newspaper advertising - Al-Siyami, Alawiya W. I. (Journal of Modern Languages, 2017)
To gain the readers’ interest positively is certainly the ultimate goal in advertising. This is achieved, as Sillars (1991) explained, through expressing values to the knowledge of, and mostly appreciated by the readers to promote a brand or service. No strategies serving such a goal better than intertextuality. Fairclough (1992), Cook (2001), and many others have illustrated the use of intertextuality in the act of producing and comprehending references within the textual feature of the new text with references to previous texts that share its context and form. This study explores the different ways in which intertextuality is realized in the advertising of a Saudi newspaper. Focusing on ads with textual features which display social interactional meaning and indicate cultural values or reinforces a social behavior, the data showed religious and registered expressions, symbols and images within the local culture of the Saudi society that were prominently used as intertextual references. They presented the promoted product relevant to the identity of the society in the discourse of the advertisements. Intertextuality is an effective means to arouse the selling of any product when associating it with an identity.